Global Health Workforce Labor Market Projections for 2030 - Liua, Jenny X; Goryakin, Yevgeniy; Maeda, Akiko; Bruckner, Tim; Scheffler, Richard (World Bank, Washington, DC, 2016)
In low- and middle-income countries, scaling essential health interventions to achieve health development targets is constrained by the lack of skilled health professionals to deliver services. This paper takes a labor market approach to project future health workforce demand based on an economic model that projects economic growth, demographics, and health coverage, and using health workforce data (1990-2013) for 165 countries from the World Health Organization's Global Health Observatory. The demand projections are compared with the projected growth in health worker supply and health worker "needs" as estimated by the World Health Organization to achieve essential health coverage. The model predicts that by 2030 global demand for health workers will rise to 80 million workers, double the current (2013) stock of health workers. The supply of health workers is expected to reach 65 million over the same period, resulting in a worldwide shortage of 15 million health workers. Growth in the demand for health workers will be highest among upper-middle-income countries, driven by economic growth and population growth and aging, resulting in the largest predicted shortages, which may fuel global competition for skilled health workers. Middle-income countries will face workforce shortages because their demand will exceed supply. By contrast, low-income countries will face low growth in demand and supply, but they will face workforce shortages because their needs will exceed supply and demand. In many low-income countries, demand may stay below projected supply, leading to the paradoxical phenomenon of unemployed ("surplus") health workers in those countries facing acute "needs-based" shortages.